A randomized controlled trial of brief interventions to reduce drug use among adults in a low‐income urban emergency department: the HealthiER You study. (7th March 2017) - Blow, Frederic C.; Walton, Maureen A.; Bohnert, Amy S. B.; Ignacio, Rosalinda V.; Chermack, Stephen; Cunningham, Rebecca M.; Booth, Brenda M.; Ilgen, Mark; Barry, Kristen L.
Abstract: Aims: To examine efficacy of drug brief interventions (BIs) among adults presenting to a low‐income urban emergency department (ED). Design: Randomized controlled trial on drug use outcomes at 3, 6 and 12 months. Participants were assigned to (1) computer‐delivered BI (Computer BI), (2) therapist‐delivered, computer‐guided BI (Therapist BI) or (3) enhanced usual care (EUC‐ED) for drug‐using adults. Participants were re‐randomized after the 3‐month assessment to either adapted motivational enhancement therapy (AMET) booster or enhanced usual care booster (EUC‐B). Setting: Patients recruited from low‐income urban emergency departments (ED) in Flint, Michigan, USA. Participants: A total of 780 ED patients reporting recent drug use, 44% males, mean age = 31 years. Interventions: Computer BI consisted of an interactive program guided by a virtual health counselor. Therapist BI included computer guidance. The EUC‐ED conditions included review of community health and HIV prevention resources. The BIs and boosters were based on motivational interviewing, focusing on reduction of drug use and HIV risk behaviors. Measurements: Primary outcome was past 90 days using drugs at 6 and 12 months and secondary outcomes were weighted drug‐days and days of marijuana use. Findings: Percentage changes in mean days used any drug from baseline to 12 months were: Computer BI + EUC‐B: –10.9%, P  = 0.0844; Therapist BI + EUC‐B: –26.7%, P  = 0.0041, for EUC‐ED + EUC‐B: –20.9, P  = 0.0011. In adjusted analyses, there was no significant interaction between ED intervention and booster AMET for primary and secondary outcomes. Compared with EUC‐ED, Therapist BI reduced number of days using any drug [95% confidence interval (CI) = −0.41, −0.07, P  = 0.0422] and weighted drug‐days (95% CI = –0.41, −0.08, P  = 0.0283). Both Therapist and Computer BI had significantly fewer number of days using marijuana compared to EUC‐ED (Therapist BI: 95% CI = –0.42, −0.06, P  = 0.0104, Computer BI: 95% CI = –0.34, −0.01, P  = 0.0406). Booster effects were not significant. Conclusions: An emergency department‐based motivational brief intervention, delivered by a therapist and guided by computer, appears to reduce drug use among adults seeking emergency department care compared with enhanced usual care.